2020
DOI: 10.1115/1.4047114
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization of a Soft Robotic Ventricular Assist Device to the Native Cardiac Rhythm Using an Epicardial Electrogram

Abstract: Soft robotic devices have been proposed as an alternative solution for ventricular assistance. Unlike conventional ventricular assist devices (VADs) that pump blood through an artificial lumen, soft robotic VADs (SRVADs) use pneumatic artificial muscles (PAM) to assist native contraction and relaxation of the ventricle. Synchronization of SRVADs is critical to ensure maximized and physiologic cardiac output. We developed a proof-of-concept synchronization algorithm that uses an epicardial electrogram as an inp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…These types of ventricular assistance can also be triggered with electrical feedback via electrocardiogram signals, or pressure driven feedback measured within the blood vessels Please do not adjust margins Please do not adjust margins to produce a closed-loop assist system to provide tailored therapy to the patient. 97…”
Section: Mechanical Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…These types of ventricular assistance can also be triggered with electrical feedback via electrocardiogram signals, or pressure driven feedback measured within the blood vessels Please do not adjust margins Please do not adjust margins to produce a closed-loop assist system to provide tailored therapy to the patient. 97…”
Section: Mechanical Stimulationmentioning
confidence: 99%
“…These types of ventricular assistance can also be triggered with electrical feedback via electrocardiogram signals, or pressure-driven feedback measured within the blood vessels to produce a closed-loop assist system to provide tailored therapy to the patient. 97 Fig. 3 Implants with fluidic shape actuation (a) Minimally invasive spinal cord stimulator using shape actuation to enable deployment using a Tuohy needle before expansion to conform to the spinal.…”
Section: Mechanical Stimulationmentioning
confidence: 99%
“…We can use the real-time heart beat signals from the surface electrogram to synchronize with the native ventricular actuation patterns. [40] Phase differences could be explored to optimize the volumetric output of the heart. With…”
Section: Doi: 101002/advs202000726mentioning
confidence: 99%
“…We can use the real‐time heart beat signals from the surface electrogram to synchronize with the native ventricular actuation patterns. [ 40 ] Phase differences could be explored to optimize the volumetric output of the heart. With improved field strength, the weight and volume of the MACP could be reduced, and the development of advanced tissue adhesives would eliminate the need for manual sutures during the experiments.…”
Section: Figurementioning
confidence: 99%
“…2,5,9 In recent work, our group has suggested the concept of soft robotic ventricular assist devices. 1,10 Taking advantage of recent advances in soft robotics, we have shown that septally braced soft epicardial actuators can be precisely actuated in synchrony with the failing heart, to augment function. 10 Light, compact, and with minimal blood contact, these devices provide pulsatile augmentation of the native ventricular ejection by mechanically approximating the septum and ventricular free wall, making use of the native cardiovascular chambers without the requirement to reroute blood flow.…”
Section: Introductionmentioning
confidence: 99%